Range of Anxiety: From Normal Concerns to Disorders - Aulya, Ayu Syarifatul (Maliki Interdisciplinary Journal, 2025)
This article examines the spectrum of anxiety, from normal worry to clinical disorders, with a particular focus on its prevalence among adolescents. Using qualitative methodology through literature review, the study analyzes the distinguishing characteristics between normal anxiety and anxiety disorders. Normal anxiety serves as an adaptive response that enhances alertness and motivation, while anxiety disorders are characterized by persistent symptoms that significantly impair daily functioning. The research identifies physical symptoms (such as palpitations and tremors), psychological manifestations (including excessive worry and difficulty concentrating), and behavioral indicators (like avoidance behaviors and compulsive checking) that characterize anxiety disorders. The article categorizes six main types of anxiety disorders: Generalized Anxiety Disorder, Panic Disorder, Social Anxiety Disorder, Specific Phobias, Obsessive-Compulsive Disorder, and Post-Traumatic Stress Disorder. The study concludes with evidence-based interventions including psychotherapy approaches like Cognitive Behavioral Therapy, pharmacological treatments, and lifestyle modifications that can effectively manage anxiety disorders.